(untitled) (Journal of Economic Research & Business Administration, 2017)
The transition of the economy to an innovative development path requires the state to pay special attention to the search for and use of internal development reserves, based on the available scientific, historical, cultural and natural potential.One of the ways is to improve the management of tourism and create a competitive tourism product.Therefore, we believe that there was a need to clarify the content of tourism management as an independent field of scientific knowledge. Tourism is a unique social and economic phenomenon that encompasses life and activity of people all over the world as a sphere of recreation and leisure, personal development, entrepreneurship, professional interests and employment, and regional development.Tourism has become a lifestyle of modern society, a way of knowing the world and a significant part of the world economy. The purpose of public management of tourism activities is that the state, recognizing tourism activity as one of the priority branches of the economy of the state, promotes the development of tourism activities and creates favorable conditions for its functioning, determines and supports priority directions.The article deals with theoretical aspects of the concept of «tourism», topical issues of the development of tourism management systems at various levels, as well as improving the efficiency of the tourist sector at the state level.